2021
DOI: 10.1016/j.btre.2021.e00663
|View full text |Cite
|
Sign up to set email alerts
|

A review on allopathic and herbal nanofibrous drug delivery vehicles for cancer treatments

Abstract: Highlights The life-threatening side effects of cancer treatment are addressed using nano-formulations and combinational therapy. Herbal drugs displayed potency in curing cancer using a nanofiber based device. Allopathic anti-cancer drugs can be delivered at a targeted site using a nanofiber based drug carrier which improves bioavailability to a great extent. A combination of an herbal and allopathic anticancer drug could be a possible l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 82 publications
1
11
0
Order By: Relevance
“…In other words, the hydrophilic polymers have been shown to accelerate the rate of DNA release by forming water channels within the matrix. Recent studies [32][33][34] have reported the ability of copolymers containing PLA and PEG components to control drug release, which is in support of the results of this study. The ability to penetrate and transport PLA-PEG/Chitosan-FA/DNA nanoparticles into MCF-7 cells was demonstrated using uorescent microscopy images (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In other words, the hydrophilic polymers have been shown to accelerate the rate of DNA release by forming water channels within the matrix. Recent studies [32][33][34] have reported the ability of copolymers containing PLA and PEG components to control drug release, which is in support of the results of this study. The ability to penetrate and transport PLA-PEG/Chitosan-FA/DNA nanoparticles into MCF-7 cells was demonstrated using uorescent microscopy images (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Given that the premise for gene transfer by these nanocarriers is dependent on the phenomena of endocytosis, and that intracellular nucleases destroy more than 99 percent of the DNA entering the cell, as a result, in gene therapy research, protecting DNA from harmful enzymes is critical [33]. Previous studies have demonstrated that polycations constitute a physical barrier to restriction enzyme binding due to their complexation with DNA, therefore shielding DNA from digestion by these enzymes [34].The ability of PLA-PEG/Chitosan-FA/DNA nanoparticles to penetrate and safely release DNA into MCF-7 cells was demonstrated by uorescent microscopy images of MCF-7 cells treated with these nanoparticles (Fig. 4, E).…”
Section: Discussionmentioning
confidence: 99%
“…Nanotechnology is the novel and targeted drug delivery system for treatment of cancer and the future of medical science. Nanostructures including nanoparticles, liposomes, dendrimers, and micelles have been employed as controlled delivery systems for the treatment of cancer [ 4 ]. For many years, herbal remedies have been used and are still used as the primary form of healthcare in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have combined the as-synthesized magnetic nanoparticles with various polymers to produce composite nanofibers through electrospinning [ 30 , 31 ]. In this study, we emphasized the fabrication of nanofibers embedded with magnetic particles of two distinct kinds, which provide different magnetic responses depending on the required applications.…”
Section: Introductionmentioning
confidence: 99%